Invincible : the 10 lies you learn growing up with domestic violence, and the truths to set you free - Martin, Brian F. (Perigee, 2014)
"According to UNICEF, growing up with domestic violence is one of the most pervasive human rights violations in the world, affecting more than a billion people. Yet, too few people are aware of the profound impact it can have. Invincible seeks to change this lack of awareness and understanding with a compelling look at this important issue, informing and inspiring anyone who grew up living with domestic violence--and those who love them, work with them, teach them, and mentor them. Through powerful first-person stories, including the author's own experiences, as well as insightful commentary based on the most recent social science and psychology research, Invincible not only offers a deeper understanding of the concerns and challenges of domestic violence, but also provides proven strategies everyone can use to reclaim their lives and futures."--